Assessment of the Maritime General Education Curriculum, Admission Policy and Faculty Status towards a Proposed Maritime Program - Taberdo, Ana Liza Gruspe (JPAIR Institutional Research, 2017)
The Philippines Education Reform envisions the quality of Filipino graduates to be in parallel assessment along with competitors in regional and global employment communities and educational opportunities. Thus, the Maritime Educational Institutions are obliged to assess their present educational set-up and examine the necessary changes in its general education curriculum, admission policy and faculty status to ensure smooth transition with least disruption for the shift in AY 2018. Qualitative design using document analysis and interviews was utilized. Data revealed that subjecting the current maritime curriculum to the provisions of K+12 program and CHED Memo Order No 20. S.2013 will result to the reduction of general education courses from 64 units to 36 units. English Speech Communication with IMO SMCP, World Geography and Maritime Economics should be added. The current age requirement should be adjusted from 16-22 to 18-24 years old. Those from the STEM track and the maritime high school are best suited for the maritime courses. A bridging program should be given to graduates of other tracks. The current admission test should include Philippine History and Culture, and Economics. The Human Resource Department should identify any administrative positions GE faculty may qualify or empower them in research activities. The Maritime educational Institutions should revise the GE curriculum, admission policy and faculty status.